PENERAPAN PERTAMINA WAY PADA SPBU 14.285.680 HJ. T. UMISALMAH PASIR PUTIH PASIR PENGARAIAN - -, Hasbi (Jurnal Mahasiswa Prodi SI Manajemen, 2013)
This paper is entitled “Penerapan Pertamina Way pada SPBU 14.285.680 HJ. T. Umisalamah Pasir Putih Pasir Pengaraian” the purpose of the research is to explain the result of research by narasi, where the gathered data is explained in structured sentence systematically.Since 2008 SPBU 14.285.680 Hj. T Umisalamah Pasir Pengaraian have run program PT. Pertamina to apply standar service that consist of 5 element, there are staff service, facility and equipment, consistent physical format, offer of product and service of addition with operator applying 3S + 3P (Greeting, Smile, admonish and good measuring, good the return and good service)The effort of SPBU 14.285.680 Hj. T. Umisalmah Pasir Pengaraian in maintaining Pasti Pas Certificate is hard work, environmental friendliness, improving the quality of service, and doing assessment of job. In order to until know SPBU 14.285.680 Hj. T. Umisalmah Pasir Pengaraian can execute program Pertamina Way and Pasti Pas certificates.